(untitled) (Euro-Asia Conferences, 2021)
The article presents the results of scientific research aimed at studying the technology of dyeing woolen fabrics with irritants. An aromatic hydroxylase phynocylose with an aromatic hydroxylase group consisting of an aromatic hydroxylase in the keratin macromolecule, which is used as a nitrogen-fixing agent in the dyeing of cellulose fibers with water-insoluble dyes in wool dye. The position of the color L *, a *, b * in the color field is determined, and the color, saturation and brightness of the color depend on the environment of the dyeing process